If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -0.7 = 8.67 Reorder the terms: -0.7 + x = 8.67 Solving -0.7 + x = 8.67 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '0.7' to each side of the equation. -0.7 + 0.7 + x = 8.67 + 0.7 Combine like terms: -0.7 + 0.7 = 0.0 0.0 + x = 8.67 + 0.7 x = 8.67 + 0.7 Combine like terms: 8.67 + 0.7 = 9.37 x = 9.37 Simplifying x = 9.37
| 3x-3=-6+4x | | -5=-7x+8x | | (13t+7)(6t-7)=0 | | (y-6)-(y+7)=2y | | g/3-7=-15 | | 2u+3(u+6)=-12 | | 3p-1+5= | | 60=-8m | | 3x+1=-22-x | | -7v+2(v-7)=36 | | 7(3x-7)=2.33 | | 8x-2=3(x-1)+5x-5 | | -4+4x=3x-2 | | y=x^2-6x+24 | | 6-6x=6x-9x+12 | | 7(2n-3)-1=-92 | | 4t^3=-27t | | -2=6(v-2)-8v | | y=8x^2-48x+192 | | 28+21m=42+14m | | 3x+2y+8x= | | 11x+14=x | | (3x+4)+(2x-3)= | | -3x+6+5x= | | (3x+2)(4x-3)= | | 2.89=logx | | 2-(5y-4)=y+12 | | 400=8(6v+2) | | 7(3x-7)= | | 5(2z+1)-z-22= | | (3x+4)+(2x-3)(5x+1)= | | 5+2(3x-4)=2x+9 |